Transforming care for patients living with diabetes in rural Mexico: a qualitative study of patient and provider experiences and perceptions of shared medical appointments - Martha de Lourdes Arrieta-Canales; Joia Mukherjee; Hannah Gilbert; Hugo Flores; Melania Muñoz; Zeus Aranda; Samuel DiChiara; Carolina Noya (Taylor & Francis Group, 2023)
Background Global prevalence of diabetes is increasing, causing widespread morbidity, mortality and increased healthcare costs. Providing quality care in a timely fashion to people with diabetes in low-resource settings can be challenging. In the underserved state of Chiapas, Mexico, which has some of the lowest diabetes detection and control rates in the country, there is a need to implement strategies that improve care for patients with diabetes. One such strategy is shared medical appointments (SMAs), a patient-centred approach that has proven effective in fostering patient engagement and comprehensive care delivery among underserved populations. Objective This study aimed to understand the perceptions, experiences and insights of both patients living with diabetes and healthcare providers, who took part in a pilot SMA strategy implemented in five outpatient clinics in rural Chiapas. Methods Following an exploratory qualitative approach, we conducted 50 in-depth interviews with patients and providers involved in diabetes SMAs and five focus group discussions with community health workers providing patient support and education. Results The implementation of an SMA model changed how diabetes care is perceived, structured and delivered. Patients felt sheltered by group interactions based on trust, which allowed for the exchange of experiences, learning and increased engagement in treatment and lifestyle changes. Providers gained insights into their patients' context and lived experiences, which resulted in improved rapport and quality of care. SMAs also restructured some operational aspects in the clinics and fostered the sharing of power and responsibilities amongst the staff. Conclusions The SMAs model transformed care by providing a patient-centred, collaborative approach to diabetes care, education and support. Additionally, it reshaped the health-care team resulting in power-shifting and role-sharing among members of the interdisciplinary team. We therefore encourage decision-makers to expand the use of SMAs to improve care for patients with diabetes in low-resource settings.